Anti-aging PE pipe and preparation method thereof
The aging resistance and flame retardant properties of PE materials are solved by cross-linking reactions of components such as low-density polyethylene, maleic anhydride grafted polyethylene, phosphorus-containing flame retardant and modified nano-silica in PE tubes. The problem of insufficient results has achieved good aging resistance and flame retardant performance of PE tubes, expanding its application areas.
Patent Information
- Application Number
- CN202411584460.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The poor aging resistance and flame retardant properties of existing PE materials limit their application areas, especially the flame retardant effect has not been improved.
The aging-resistant PE tube is prepared by cross-linking reaction and click chemical method to improve its flame retardant performance and Mechanical properties.
It has achieved good aging resistance, flame retardant and tensile resistance of PE tubes, which has significantly improved the potential of its application field.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to an aging-resistant PE pipe and a preparation method thereof. Background Art
[0002] PE material is a thermoplastic resin made by ethylene polymerization. It has excellent characteristics such as low temperature resistance, chemical stability, corrosion resistance, and strong electrical insulation. It is widely used in the manufacture of films, packaging materials, pipes, wires and cables, etc. However, its aging resistance and flame retardant properties are poor, which greatly limits its application field. Therefore, how to avoid this phenomenon is the key to solving the problem. For example, patent CN109370013A discloses an antibacterial and aging-resistant PE water supply pipe and its preparation method. The antibacterial and aging-resistant PE water supply pipe of the invention has good antibacterial effect and good aging resistance, but its flame retardant effect has not been improved. Summary of the invention
[0003] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides an aging-resistant PE pipe and a preparation method thereof, which has good aging-resistant, flame-retardant and tensile-resistant properties.
[0004] (II) Technical solution To achieve the above-mentioned purpose, the present invention provides the following technical scheme: an aging-resistant PE pipe, comprising the following components by weight: 60-80 parts by weight of low-density polyethylene, 15-25 parts by weight of maleic anhydride grafted polyethylene, 5-12 parts by weight of phosphorus-containing flame retardant, 7-13 parts by weight of modified nano-silica, 0.1-0.3 parts by weight of antioxidant 1010, and 0.2-0.4 parts by weight of paraffin oil lubricant.
[0005] Preferably, the preparation method of the phosphorus-containing flame retardant is: (1) Add sulfaguanidine to a reactor containing anhydrous ethanol, and after it is completely dissolved, add p-hydroxymethylbenzaldehyde to it, stir and react at 70-90°C for 8-10 hours, then continue to add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to it, react at 75-85°C for 14-18 hours, and after the reaction, cool, filter and dry to obtain intermediate 1; (2) Add 4-(2-methylpropenyl)carbonyloxyphenylboronic acid and hexachlorocyclotriphosphazene to acetone solvent, stir to dissolve, introduce nitrogen protection, react at 65-80°C for 2-5h, and after the reaction is completed, rotary evaporate to obtain boron-modified hexachlorocyclotriphosphazene; (3) Adding boron-modified hexachlorocyclotriphosphazene to N,N-dimethylformamide solvent, stirring and dispersing, adding thioglycolic acid and benzoin dimethyl ether photoinitiator, irradiating with ultraviolet light for 3-7 hours at 20-45° C., centrifuging, washing and drying to obtain carboxylated boron-modified hexachlorocyclotriphosphazene; (4) Add the carboxylated boron-containing hexachlorocyclotriphosphazene and intermediate 1 into N,N-dimethylformamide solvent, stir evenly, continue to add p-toluenesulfonic acid catalyst, react at 75-90°C for 5-8h, and then distill under reduced pressure, wash and dry to obtain a phosphorus-containing flame retardant.
[0006] In the above reaction process, the amino group in sulfaguanidine and the aldehyde group in p-hydroxymethylbenzaldehyde undergo a condensation reaction to introduce a double bond, and then an addition reaction is carried out with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to introduce a hydroxyl group, thereby obtaining an intermediate 1; the boric acid group in 4-(2-methylpropenyl)carbonyloxyphenylboronic acid reacts with the chlorine in hexachlorocyclotriphosphazene to introduce an olefin group, thereby obtaining a boron-modified hexachlorocyclotriphosphazene, and then a click reaction is carried out with the thiol group in thioglycolic acid to introduce a carboxyl group, thereby obtaining a carboxylated boron-containing hexachlorocyclotriphosphazene; the carboxyl group in the carboxylated boron-containing hexachlorocyclotriphosphazene undergoes an esterification reaction with the hydroxyl group in the intermediate 1, thereby obtaining a phosphorus-containing flame retardant.
[0007] Preferably, the mass ratio of sulfaguanidine, p-hydroxymethylbenzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in (1) is 1:2.1-2.3:1.6-2.4.
[0008] Preferably, the mass ratio of 4-(2-methylpropenyl)carbonyloxyphenylboronic acid to hexachlorocyclotriphosphazene in (2) is 3.2-3.5:1.
[0009] Preferably, the mass ratio of the boron-modified hexachlorocyclotriphosphazene, thioglycolic acid and benzoin dimethyl ether photoinitiator in (3) is 1:2.5-3.6:0.01-0.03.
[0010] Preferably, the mass ratio of carboxylated boron-containing hexachlorocyclotriphosphazene, intermediate 1, and p-toluenesulfonic acid catalyst in (4) is 1:2.2-2.8:0.02-0.05.
[0011] Preferably, the preparation method of the modified nano-silicon dioxide is: S1. At 20-35°C, anhydrous ethanol and 20-30% ammonia water are added to a reactor filled with deionized water, and then 4-7.2 g of ethyl orthosilicate is added thereto, stirred for 3-6 hours, mixed evenly, filtered, dried, and then the obtained product is placed in a sodium hydroxide solution, heated in a water bath at 70-90°C for 2-4 hours, cooled to room temperature, washed with deionized water, and dried to obtain hydroxylated silica; S2. Add 3,3-dimethylglutaryl chloride, intermediate 1 and hydroxylated silica to N,N-dimethylformamide solvent, stir for 10-15 minutes, then continue to add pyridine catalyst, react at 70-95° C. for 7-13 hours, and then perform reduced pressure distillation and washing to obtain modified nano-silica.
[0012] In the above reaction process, the acyl chloride group in 3,3-dimethylglutaryl chloride reacts with the hydroxyl group in the intermediate 1 and the hydroxyl group in the hydroxylated silica to obtain modified nano-silica.
[0013] Preferably, the mass ratio of 3,3-dimethylglutaryl chloride, intermediate 1, hydroxylated silica, and pyridine catalyst in S2 is 0.6-0.8:1:1.1-1.2:0.01-0.03.
[0014] Preferably, the preparation method of the aging-resistant PE pipe is: low-density polyethylene, maleic anhydride grafted polyethylene, phosphorus-containing flame retardant, modified nano-silica, antioxidant 1010, and paraffin oil lubricant are placed in a high-speed mixer and mixed evenly, extruded into granules in a twin-screw extruder, the blending temperature is 180-190°C, the extrusion temperature is 170-180°C, dried, and injection molded by an injection molding machine to obtain an aging-resistant PE pipe.
[0015] 3. Beneficial technical effects The invention obtains an aging-resistant PE pipe by mixing low-density polyethylene, maleic anhydride grafted polyethylene, phosphorus-containing flame retardant, modified nano silicon dioxide, antioxidant 1010 and paraffin oil lubricant in a high-speed mixer, extruding and granulating in a twin-screw extruder, drying and injection molding by an injection molding machine.
[0016] During the mixing process, the hydroxyl groups in the phosphorus-containing flame retardant and modified nano-silica react with the anhydride groups in the maleic anhydride grafted polyethylene, cross-linking each other to form a molecular cross-linking network, which improves its mechanical properties and also improves its compatibility with polyethylene, making it evenly distributed in the PE pipe. The phosphorus, sulfur, guanidine, nitrogen, boron, and nano-silica groups contained in the phosphorus-containing flame retardant and modified nano-silica all have good flame retardancy and together constitute a flame retardant system; the nano-silica has good aging resistance. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1 (1) Add 1 g of sulfaguanidine to a reactor containing 60 ml of anhydrous ethanol. After the mixture is completely dissolved, add 2.1 g of p-hydroxymethylbenzaldehyde and stir the mixture at 70°C for 8 h. Then, add 1.6 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and react at 75°C for 14 h. After the mixture is cooled, filtered and dried, intermediate 1 is obtained. (2) Add 3.2 g of 4-(2-methylpropenyl)carbonyloxyphenylboronic acid and 1 g of hexachlorocyclotriphosphazene into 50 ml of acetone solvent, stir to dissolve, introduce nitrogen protection, react at 65 ° C for 2 h, and after the reaction is completed, rotary evaporate to obtain boron-modified hexachlorocyclotriphosphazene; (3) Add 1 g of boron-modified hexachlorocyclotriphosphazene to 65 ml of N,N-dimethylformamide solvent, stir and disperse, then add 2.5 g of thioglycolic acid and 0.01 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 20°C for 3 h, centrifuge, wash and dry to obtain carboxylated boron-modified hexachlorocyclotriphosphazene; (4) Add 1 g of carboxylated boron-containing hexachlorocyclotriphosphazene and 2.2 g of intermediate 1 into 60 ml of N,N-dimethylformamide solvent, stir evenly, continue to add 0.02 g of p-toluenesulfonic acid catalyst, react at 75 ° C for 5 h, and then distill under reduced pressure, wash and dry to obtain a phosphorus-containing flame retardant; (5) At 20°C, add 30 ml of anhydrous ethanol and 20% ammonia water into a reactor containing 75 ml of deionized water, then add 4 g of ethyl orthosilicate, stir for 3 h, mix evenly, filter and dry, then place the obtained product in a sodium hydroxide solution, heat in a water bath at 70°C for 2 h, cool to room temperature, wash with deionized water, and dry to obtain hydroxylated silica; (6) Add 0.6 g of 3,3-dimethylglutaryl chloride, 1 g of intermediate 1 and 1.1 g of hydroxylated silica to 70 ml of N,N-dimethylformamide solvent, stir for 10 min, then continue to add 0.01 g of pyridine catalyst, react at 70 ° C for 7 h, and then perform vacuum distillation and washing to obtain modified nano-silica; (7) 60 g of low-density polyethylene, 15 g of maleic anhydride grafted polyethylene, 5 g of phosphorus-containing flame retardant, 7 g of modified nano-silica, 0.1 g of antioxidant 1010, and 0.2 g of paraffin oil lubricant were placed in a high-speed mixer and mixed evenly, and extruded into granules in a twin-screw extruder at a blending temperature of 180°C and an extrusion temperature of 170°C. The mixture was dried and injection molded by an injection molding machine to obtain an aging-resistant PE pipe.
[0019] Example 2 (1) 1 g of sulfaguanidine was added to a reactor containing 80 ml of anhydrous ethanol. After the mixture was completely dissolved, 2.3 g of p-hydroxymethylbenzaldehyde was added thereto. The mixture was stirred and reacted at 90°C for 10 h. Then, 2.4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added thereto. The mixture was reacted at 85°C for 18 h. After the reaction was completed, the mixture was cooled, filtered and dried to obtain intermediate 1. (2) Add 3.5 g of 4-(2-methylpropenyl)carbonyloxyphenylboronic acid and 1 g of hexachlorocyclotriphosphazene into 100 ml of acetone solvent, stir to dissolve, introduce nitrogen protection, react at 80 ° C for 5 h, and after the reaction is completed, rotary evaporate to obtain boron-modified hexachlorocyclotriphosphazene; (3) Add 2 g of boron-modified hexachlorocyclotriphosphazene to 90 ml of N,N-dimethylformamide solvent, stir and disperse, then add 7.2 g of thioglycolic acid and 0.06 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 45°C for 7 h, centrifuge, wash and dry to obtain carboxylated boron-modified hexachlorocyclotriphosphazene; (4) Add 1.5 g of carboxylated boron-containing hexachlorocyclotriphosphazene and 4.2 g of intermediate 1 into 80 ml of N,N-dimethylformamide solvent, stir evenly, continue to add 0.075 g of p-toluenesulfonic acid catalyst, react at 90 ° C for 8 h, and then distill under reduced pressure, wash and dry to obtain a phosphorus-containing flame retardant; (5) At 35°C, add 60 ml of anhydrous ethanol and 30% ammonia water into a reactor containing 90 ml of deionized water, then add 7.2 g of ethyl orthosilicate, stir for 6 h, mix evenly, filter and dry, then place the obtained product in a sodium hydroxide solution, heat in a water bath at 90°C for 4 h, cool to room temperature, wash with deionized water, and dry to obtain hydroxylated silica; (6) Add 0.8 g of 3,3-dimethylglutaryl chloride, 1 g of intermediate 1 and 1.2 g of hydroxylated silica to 95 ml of N,N-dimethylformamide solvent, stir for 15 min, then continue to add 0.03 g of pyridine catalyst, react at 95 °C for 13 h, and then perform vacuum distillation and washing to obtain modified nano-silica; (7) 80 g of low-density polyethylene, 25 g of maleic anhydride grafted polyethylene, 12 g of phosphorus-containing flame retardant, 13 g of modified nano-silica, 0.3 g of antioxidant 1010, and 0.4 g of paraffin oil lubricant were placed in a high-speed mixer and mixed evenly, and extruded into granules in a twin-screw extruder at a blending temperature of 190°C and an extrusion temperature of 180°C. The mixture was dried and injection molded by an injection molding machine to obtain an aging-resistant PE pipe.
[0020] Example 3 (1) Add 1 g of sulfaguanidine to a reactor containing 60-80 ml of anhydrous ethanol. After the mixture is completely dissolved, add 2.1-2.3 g of p-hydroxymethylbenzaldehyde, stir and react at 70-90° C. for 8-10 h, then continue to add 1.6-2.4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, react at 75-85° C. for 14-18 h, and after completion, cool, filter and dry to obtain intermediate 1; (2) Add 3.2-3.5 g of 4-(2-methylpropenyl)carbonyloxyphenylboronic acid and 1 g of hexachlorocyclotriphosphazene into 50-100 ml of acetone solvent, stir to dissolve, introduce nitrogen protection, react at 65-80° C. for 2-5 h, and after the reaction is completed, rotary evaporate to obtain boron-modified hexachlorocyclotriphosphazene; (3) Add 1.5 g of boron-modified hexachlorocyclotriphosphazene to 75 ml of N,N-dimethylformamide solvent, stir and disperse, then add 3.6 g of thioglycolic acid and 0.04 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 35° C. for 5 h, centrifuge, wash and dry to obtain carboxylated boron-modified hexachlorocyclotriphosphazene; (4) Add 1.25 g of carboxylated boron-containing hexachlorocyclotriphosphazene and 2.8 g of intermediate 1 into 70 ml of N,N-dimethylformamide solvent, stir evenly, continue to add 0.06 g of p-toluenesulfonic acid catalyst, react at 82 ° C for 6 h, and then distill under reduced pressure, wash and dry to obtain a phosphorus-containing flame retardant; (5) At 30°C, add 45 ml of anhydrous ethanol and 25% ammonia water into a reactor containing 80 ml of deionized water, then add 6 g of ethyl orthosilicate, stir for 4 h, mix evenly, filter and dry, then place the obtained product in a sodium hydroxide solution, heat in a water bath at 80°C for 3 h, cool to room temperature, wash with deionized water, and dry to obtain hydroxylated silica; (6) Add 0.7 g of 3,3-dimethylglutaryl chloride, 1 g of intermediate 1 and 1.15 g of hydroxylated silica to 80 ml of N,N-dimethylformamide solvent, stir for 12 min, then continue to add 0.02 g of pyridine catalyst, react at 85 °C for 10 h, and then perform vacuum distillation and washing to obtain modified nano-silica; (7) 70 g of low-density polyethylene, 20 g of maleic anhydride grafted polyethylene, 9 g of phosphorus-containing flame retardant, 10 g of modified nano-silica, 0.2 g of antioxidant 1010, and 0.3 g of paraffin oil lubricant were placed in a high-speed mixer and mixed evenly, and extruded into granules in a twin-screw extruder at a blending temperature of 185°C and an extrusion temperature of 175°C. The mixture was dried and injection molded by an injection molding machine to obtain an aging-resistant PE pipe.
[0021] Example 4 (1) Add 1 g of sulfaguanidine to a reactor containing 60 ml of anhydrous ethanol. After the mixture is completely dissolved, add 2.1 g of p-hydroxymethylbenzaldehyde and stir the mixture at 70°C for 8 h. Then, add 1.6 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and react at 75°C for 14 h. After the mixture is cooled, filtered and dried, intermediate 1 is obtained. (2) Add 3.2 g of 4-(2-methylpropenyl)carbonyloxyphenylboronic acid and 1 g of hexachlorocyclotriphosphazene into 50 ml of acetone solvent, stir to dissolve, introduce nitrogen protection, react at 65 ° C for 2 h, and after the reaction is completed, rotary evaporate to obtain boron-modified hexachlorocyclotriphosphazene; (3) Add 2 g of boron-modified hexachlorocyclotriphosphazene to 90 ml of N,N-dimethylformamide solvent, stir and disperse, then add 7.2 g of thioglycolic acid and 0.06 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 45°C for 7 h, centrifuge, wash and dry to obtain carboxylated boron-modified hexachlorocyclotriphosphazene; (4) Add 1.5 g of carboxylated boron-containing hexachlorocyclotriphosphazene and 4.2 g of intermediate 1 into 80 ml of N,N-dimethylformamide solvent, stir evenly, continue to add 0.075 g of p-toluenesulfonic acid catalyst, react at 90 ° C for 8 h, and then distill under reduced pressure, wash and dry to obtain a phosphorus-containing flame retardant; (5) At 30°C, add 45 ml of anhydrous ethanol and 25% ammonia water into a reactor containing 80 ml of deionized water, then add 6 g of ethyl orthosilicate, stir for 4 h, mix evenly, filter and dry, then place the obtained product in a sodium hydroxide solution, heat in a water bath at 80°C for 3 h, cool to room temperature, wash with deionized water, and dry to obtain hydroxylated silica; (6) Add 0.7 g of 3,3-dimethylglutaryl chloride, 1 g of intermediate 1 and 1.15 g of hydroxylated silica to 80 ml of N,N-dimethylformamide solvent, stir for 12 min, then continue to add 0.02 g of pyridine catalyst, react at 85 °C for 10 h, and then perform vacuum distillation and washing to obtain modified nano-silica; (7) 70 g of low-density polyethylene, 20 g of maleic anhydride grafted polyethylene, 9 g of phosphorus-containing flame retardant, 10 g of modified nano-silica, 0.2 g of antioxidant 1010, and 0.3 g of paraffin oil lubricant were placed in a high-speed mixer and mixed evenly, and extruded into granules in a twin-screw extruder at a blending temperature of 185°C and an extrusion temperature of 175°C. The mixture was dried and injection molded by an injection molding machine to obtain an aging-resistant PE pipe.
[0022] Example 5 (1) 1 g of sulfaguanidine was added to a reactor containing 80 ml of anhydrous ethanol. After the mixture was completely dissolved, 2.3 g of p-hydroxymethylbenzaldehyde was added thereto. The mixture was stirred and reacted at 90°C for 10 h. Then, 2.4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added thereto. The mixture was reacted at 85°C for 18 h. After the reaction was completed, the mixture was cooled, filtered and dried to obtain intermediate 1. (2) Add 3.5 g of 4-(2-methylpropenyl)carbonyloxyphenylboronic acid and 1 g of hexachlorocyclotriphosphazene into 100 ml of acetone solvent, stir to dissolve, introduce nitrogen protection, react at 80 ° C for 5 h, and after the reaction is completed, rotary evaporate to obtain boron-modified hexachlorocyclotriphosphazene; (3) Add 1.5 g of boron-modified hexachlorocyclotriphosphazene to 75 ml of N,N-dimethylformamide solvent, stir and disperse, then add 3.6 g of thioglycolic acid and 0.04 g of benzoin dimethyl ether photoinitiator, irradiate with ultraviolet light at 35° C. for 5 h, centrifuge, wash and dry to obtain carboxylated boron-modified hexachlorocyclotriphosphazene; (4) Add 1.25 g of carboxylated boron-containing hexachlorocyclotriphosphazene and 2.8 g of intermediate 1 into 70 ml of N,N-dimethylformamide solvent, stir evenly, continue to add 0.06 g of p-toluenesulfonic acid catalyst, react at 82 ° C for 6 h, and then distill under reduced pressure, wash and dry to obtain a phosphorus-containing flame retardant; (5) At 20°C, add 30 ml of anhydrous ethanol and 20% ammonia water into a reactor containing 75 ml of deionized water, then add 4 g of ethyl orthosilicate, stir for 3 h, mix evenly, filter and dry, then place the obtained product in a sodium hydroxide solution, heat in a water bath at 70°C for 2 h, cool to room temperature, wash with deionized water, and dry to obtain hydroxylated silica; (6) Add 0.6 g of 3,3-dimethylglutaryl chloride, 1 g of intermediate 1 and 1.1 g of hydroxylated silica to 70 ml of N,N-dimethylformamide solvent, stir for 10 min, then continue to add 0.01 g of pyridine catalyst, react at 70 ° C for 7 h, and then perform vacuum distillation and washing to obtain modified nano-silica; (7) 60 g of low-density polyethylene, 15 g of maleic anhydride grafted polyethylene, 5 g of phosphorus-containing flame retardant, 7 g of modified nano-silica, 0.1 g of antioxidant 1010, and 0.2 g of paraffin oil lubricant were placed in a high-speed mixer and mixed evenly, and extruded into granules in a twin-screw extruder at a blending temperature of 180°C and an extrusion temperature of 170°C. The mixture was dried and injection molded by an injection molding machine to obtain an aging-resistant PE pipe.
[0023] Comparative Example 1 The difference between this comparative example and Example 5 is that hexachlorocyclotriphosphazene is used instead of the phosphorus-containing flame retardant.
[0024] Comparative Example 2 The difference between this comparative example and Example 5 is that nano silicon dioxide is used instead of modified nano silicon dioxide.
[0025] Comparative Example 3 The difference between this comparative example and Example 5 is that hexachlorocyclotriphosphazene is used instead of the phosphorus-containing flame retardant, and nano silicon dioxide is used instead of modified nano silicon dioxide.
[0026] Use an oxygen index tester to test the oxygen index of the material.
[0027] The combustion level of the material is tested using a horizontal vertical combustion tester.
[0028] The specific test results are shown in Table 1 below.
[0029] Table 1: Flame retardant test Group Oxygen index (%) UL-94 Example 1 31.4 V-0 Example 2 32.9 V-0 Example 3 31.4 V-0 Example 4 30.7 V-0 Example 5 31.6 V-0 Comparative Example 1 22.3 V-1 Comparative Example 2 21.7 V-1 Comparative Example 3 20.1 V-1 It can be seen from Table 1 that Examples 1-5 of the present invention have better flame retardant effects than Comparative Examples 1-3.
[0030] Aging resistance test: Referring to the standard GB / T3512-2001 for accelerated aging and heat resistance test of rubber in hot air, the sample to be tested was cut into dumbbell-shaped specimens, and the test specimens were placed in the aging box after the aging box was adjusted to 120°C for testing. After 72 hours, the specimens were taken out, and the aged specimens were placed in the air for environmental conditioning for 48 hours. The tensile strength of the polyurethane specimens before and after aging was tested using an electronic universal testing machine (Zwick, Germany). The specific test results are shown in Table 2 below.
[0031] Table 2: Aging resistance and tensile properties test Group Tensile strength before aging (MPa) Tensile strength after aging (MPa) Example 1 8.6 8.1 Example 2 8.9 8.3 Example 3 8.7 7.9 Example 4 8.6 7.4 Example 5 8.8 7.5 Comparative Example 1 8.4 7.1 Comparative Example 2 7.3 5.3 Comparative Example 3 7.1 5.1 It can be seen from Table 2 that Examples 1-5 and Comparative Example 1 of the present invention have better tensile resistance and aging resistance effects than Comparative Examples 2-3.
[0032] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An aging-resistant PE pipe, characterized in that: The invention comprises the following components by weight: 60-80 parts by weight of low-density polyethylene, 15-25 parts by weight of maleic anhydride grafted polyethylene, 5-12 parts by weight of phosphorus-containing flame retardant, 7-13 parts by weight of modified nano silicon dioxide, 0.1-0.3 parts by weight of antioxidant 1010, and 0.2-0.4 parts by weight of paraffin oil lubricant.
2. The aging-resistant PE pipe according to claim 1, characterized in that: The preparation method of the phosphorus-containing flame retardant is: (1) Add sulfaguanidine to a reactor containing anhydrous ethanol, and after it is completely dissolved, add p-hydroxymethylbenzaldehyde to it, stir and react at 70-90°C for 8-10 hours, then continue to add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to it, react at 75-85°C for 14-18 hours, and after the reaction, cool, filter and dry to obtain intermediate 1; (2) Add 4-(2-methylpropenyl)carbonyloxyphenylboronic acid and hexachlorocyclotriphosphazene to acetone solvent, stir to dissolve, introduce nitrogen protection, react at 65-80°C for 2-5h, and after the reaction is completed, rotary evaporate to obtain boron-modified hexachlorocyclotriphosphazene; (3) Adding boron-modified hexachlorocyclotriphosphazene to N,N-dimethylformamide solvent, stirring and dispersing, adding thioglycolic acid and benzoin dimethyl ether photoinitiator, irradiating with ultraviolet light for 3-7 hours at 20-45° C., centrifuging, washing and drying to obtain carboxylated boron-modified hexachlorocyclotriphosphazene; (4) Add the carboxylated boron-containing hexachlorocyclotriphosphazene and intermediate 1 into N,N-dimethylformamide solvent, stir evenly, continue to add p-toluenesulfonic acid catalyst, react at 75-90°C for 5-8h, and then distill under reduced pressure, wash and dry to obtain a phosphorus-containing flame retardant.
3. The aging-resistant PE pipe according to claim 2, characterized in that: The mass ratio of sulfaguanidine, p-hydroxymethylbenzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in (1) is 1:2.1-2.3:1.6-2.
4.
4. The aging-resistant PE pipe according to claim 2, characterized in that: The mass ratio of 4-(2-methylpropenyl)carbonyloxyphenylboronic acid to hexachlorocyclotriphosphazene in (2) is 3.2-3.5:
1.
5. The aging-resistant PE pipe according to claim 2, characterized in that: The mass ratio of the boron-modified hexachlorocyclotriphosphazene, thioglycolic acid and benzoin dimethyl ether photoinitiator in (3) is 1:2.5-3.6:0.01-0.
03.
6. The aging-resistant PE pipe according to claim 2, characterized in that: The mass ratio of the carboxylated boron-containing hexachlorocyclotriphosphazene, the intermediate 1, and the p-toluenesulfonic acid catalyst in (4) is 1:2.2-2.8:0.02-0.
05.
7. The aging-resistant PE pipe according to claim 1, characterized in that: The preparation method of the modified nano silicon dioxide is: S1. At 20-35°C, anhydrous ethanol and 20-30% ammonia water are added to a reactor filled with deionized water, and then 4-7.2 g of ethyl orthosilicate is added thereto, stirred for 3-6 hours, mixed evenly, filtered, and dried, and then the obtained product is placed in a sodium hydroxide solution, heated in a water bath at 70-90°C for 2-4 hours, cooled to room temperature, washed with deionized water, and dried to obtain hydroxylated silica; S2. Add 3,3-dimethylglutaryl chloride, intermediate 1 and hydroxylated silica to N,N-dimethylformamide solvent, stir for 10-15 minutes, then continue to add pyridine catalyst, react at 70-95° C. for 7-13 hours, and then perform reduced pressure distillation and washing to obtain modified nano-silica.
8. The aging-resistant PE pipe according to claim 6, characterized in that: The mass ratio of 3,3-dimethylglutaryl chloride, intermediate 1, hydroxylated silica and pyridine catalyst in S2 is 0.6-0.8:1:1.1-1.2:0.01-0.
03.
9. A method for preparing an aging-resistant PE pipe according to any one of claims 1 to 7, characterized in that: The preparation method of the aging-resistant PE pipe is as follows: low-density polyethylene, maleic anhydride grafted polyethylene, phosphorus-containing flame retardant, modified nano-silica, antioxidant 1010, and paraffin oil lubricant are placed in a high-speed mixer and mixed evenly, extruded and granulated in a twin-screw extruder, the blending temperature is 180-190° C., the extrusion temperature is 170-180° C., dried, and injection molded by an injection molding machine to obtain the aging-resistant PE pipe.
Citation Information
Patent Citations
Low-gloss flame-retardant polyethylene material and preparation method thereof
CN111286105A
Anti-aging PE material and synthesis process thereof
CN116606491A
Decorative anticorrosive coating material for concrete structure and construction process of decorative anticorrosive coating material
CN118271925A
Electronic packaging material based on epoxy resin and preparation process thereof
CN118562252A
Electronic glue containing modified butadiene rubber and preparation method thereof
CN118652649A
Cited By
Antibacterial modified plastic and preparation method thereof
CN120665370A
Anti-aging modified plastic and preparation method thereof
CN120757893A
